Effects of Using Physical Activity Applied Dancing Arts Model to Promote the Well-Being of the Elderly - Rittibul, Pravit; Chaiyasung, Phatcharaphan (Journal of Ecohumanism, 2024)
This article aimed to study Effects of using Physical Activity Applied Dancing Arts Model to Promote the Well-Being of the Elderly. This is a quantitative research using the One Group Pretest-Posttest Design model of physical activity using applied dance, and a satisfaction questionnaire. The results of the study showed that form of exercise activities using applied dance to promote the well-being of the elderly. It consists of a total of 7 activities. Independent movement principle related to emotions and feelings with music. The activity was spent 16 times, 1 hour 30 minutes each. Comparative results of the mean health scores in each aspect before and after the experimental use of the exercise activity model using applied dance poses. It was found that the mean score after the experiment was higher than before the experiment. The statistical significance at the .01 level. The satisfaction in the activities was at the highest level. This research reflects the role and importance of bringing the science and art of dancing and music to apply the principles of body movement in expression to cause development or development of the physical, emotional, social and intellectual, and most importantly is to build relationships within society between individuals.